(untitled) (SAARC Journal of Agriculture, 2022)
Fall armyworm (FAW) (Spodoptera frugiperda J.E. Smith) is a polyphagous pest, native to North and South America and is invasive in Eurasia and Africa. Life cycle and morphometric studies with the invasive population of FAW in Nepal were conducted under laboratory conditions in Chitwan, Nepal. Gravid females laid an average of 156.25 eggs per egg batch, with an average of 979.43 eggs during their whole lifetime. The average pre-oviposition period was 3.75 days, oviposition period was 3 days, the larval developmental period was 16.31 days, the pupal period was 9.69 days, and the whole life cycle (egg to egg) averaged 33 days. The average length of each instar larva from I to VI instars was 1.5, 3.6, 7.1, 11.6, 18.5, and 34.4 mm, respectively. Head capsule widths for each instar were 0.35, 0.47, 0.8, 1.37, 2.11, and 2.7 mm, respectively for instars first through sixth. Pupal and adult emergence rates were 98.9 and 97.2%, respectively, with a male to female ratio of 1:1.3. Larval mortalities of the I, II, and III instars were 70, 66, and 12%, with no mortality in the IV, V and VI instars. Adult longevity was 20.73 days for males and 22.78 days for females. These findings are useful to design an integrated management protocol of the fall armyworm. SAARC J. Agric., 20(1): 77-86 (2022)